Analysis of the Mechanism of Political Cost in the Complex Environmental Governance System - Xintao Li; Tongshun Cheng; Zaisheng Zhang; Li Zhao (Complexity)
The emergence of conflicts between environmental safety incidents and protection rights generates sizeable political costs, which endangers the legitimacy of the government as well as political security and stability. This article further examines the role of political costs in environmental issues. First, political costs in relation to environmental issues are defined. An equilibrium strategic analysis is then presented using an evolutionary game model in which the strategic behavioral choices of government, enterprises, and citizens are investigated by embedding political costs in the environmental governance system. Furthermore, the small-signal model was innovatively applied to simulate and analyze the stability of political costs under different equilibrium strategies in the system. The results show the following. (1) Pubic behavior and government are the dominant factors that impact stability and instability, respectively. Public behavior is the core element that affects political cost consumption. (2) When political costs are extremely depleted, the public will neglect economic interests, turn toward environmental interests, and choose the negative participation strategy, which destabilizes the system. (3) The political cost signal at the optimal equilibrium point not only warns the government not to take the desperate action of concealing information asymmetry but also allows the government to let go of its hands to deal with the environmental issues. Corresponding policy recommendations are proposed.